Where differentiating automobile manufacturers go wrong: strategic challenges posed by increased outsourcing. (19th January 2011) - Proff, Heike
Car manufacturers outsource production of individual components to large module suppliers, saving on costs in the short term. In the medium term, however, they sacrifice competencies. The competitive strategy they choose – either cost leadership or differentiation – determines how this conflict is resolved. This article examines the shift in competencies to module suppliers, and the likely reactions of end product manufacturers, particularly those pursuing a differentiation strategy. The article derives potential strategic actions going forward based on transaction cost theory and core competency theory, and conducts a content analysis to examine them empirically.